'On the Measurement of Social Progress and Wellbeing': A Commentary. Issue 3 (18th September 2013) - Becchetti, Leonardo
<x xml:space="preserve">Abstract</x> Creating enlightened indicators, in any case, is not enough. Their success depends on their effective adoption by local authorities and corporations for their CSR strategies. Real progress will be measured along this dimension. <boxed-text content-type="graphic" id="gpol12071-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>